2017
DOI: 10.1016/j.chom.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Polysaccharide Capsules in the Human Symbiont Bacteroides thetaiotaomicron Promote Increased Competitive Fitness in the Mouse Gut

Abstract: Summary Capsular polysaccharides (CPS) play multiple roles in protecting bacteria from host and environmental factors, and many commensal bacteria can produce multiple capsule types. To better understand the roles of different CPS in competitive intestinal colonization, we individually expressed the eight different capsules of the human gut symbiont Bacteroides thetaiotaomicron. Certain CPS were most advantageous in vivo, and increased anti-CPS IgA correlated with increased fitness of a strain expressing one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 51 publications
(75 reference statements)
6
114
1
Order By: Relevance
“…A study reported a particular capsular polysaccharides (CPS5) was found in human samples which can produce multiple capsule types to survive antibiotic therapy. (Porter et al,2017) In our study 54 (74%) strains produced capsule.…”
Section: Discussion:-supporting
confidence: 47%
“…A study reported a particular capsular polysaccharides (CPS5) was found in human samples which can produce multiple capsule types to survive antibiotic therapy. (Porter et al,2017) In our study 54 (74%) strains produced capsule.…”
Section: Discussion:-supporting
confidence: 47%
“…Bacterial cellular components (anaerobic lysate, polysaccharide capsules, or outer-membrane pili-like protein) play significant roles in the cross talk between gut symbionts and the host (Plovier et al, 2017;Porter et al, 2017;Neff et al, 2016). Amuc_1100*, a thermostable outer-membrane protein of A. muciniphila, reportedly possesses beneficial effects on reducing fat mass and improving metabolic syndrome in dietinduced obese mice (Plovier et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in signals between timescales implies that the selective forces acting on these genes are not constant and raises the possibility that adaptive mutations occurring in vivo may incur collateral fitness costs in the context of other selective forces 41,42 . This notion of competing selective forces is echoed by the well-described invertible promoters of B. fragilis, which enable rapid alternation between different outer-membrane presentations 43,44 . Interestingly, the invertible promoters control the same major pathways that we identified as undergoing positive selection (capsule synthesis and polysaccharide importers) 43,45 .…”
Section: Fig 8a-f; Methods)mentioning
confidence: 99%